Determinant of Preventive Behavior COVID-19 Among Mothers in Ogan Ilir Regency, South Sumatera Indonesia - Rahmatillah Razak; Anggun Budiastuti; Nurmalia Ermi (Faculty of Public Health, Sriwijaya University, 2022)
Coronavirus disease 2019 (COVID-19 ) is an infectious disease caused by a new coronavirus (SARS-CoV-2) and currently become a great threat and public health consent worldwide, including in Indonesia. COVID-19 infected more than three hundred million people worldwide, causing more than five million deaths. This study aimed to assess the preventive behavior, knowledge, and history of COVID-19. A cross-sectional study was carried out using secondary data of field learning experience students by the Faculty of Public Health, Sriwijaya University in 2021, the population is all mothers who have toddler in Ogan Ilir Regency and the sampling method uses purposive sampling with 1850 mothers as a respondent in Ogan Ilir Regency, South Sumatera, Indonesia. Univariate analyses were used to see the distribution of variable and bivariate analysis conducted using the Chi-Square test with a significance level of 0.05 to see the association of the variable. The result shows that 0.6% of mothers infected with COVID-19 and 0.8% of mothers who had family were positive COVID-19. More than half of respondents, 52.4%, have good preventive behavior, and 48.6% have poor preventive behavior. 53.1% of respondents had good knowledge, and 46.9% had poor knowledge regarding COVID-19. Level of knowledge (P-value 0.001) and underlying health conditions or comorbidities (P-value) were factors related to good preventive behavior. Therefore, effort must be made to increase awareness and improve knowledge related to COVID-19 by health workers.